Morpho- structure characteristics of some karst caves in Yen Mo- Tam Diep area, Ninh Binh province - Lam, Doan Dinh (VNU Journal of Science: Earth and Environmental Sciences, 2010)
Abstract. Ninh Binh province is well known as an area with famous karst landscape that likes inland HaLong Bay. An attractive and charming cave system is developed in Triasic limestones of the Dong Giao formation, created a wonderful sites for tourism. The exciting features of karst landforms in the Ninh Binh province are mogots. It is mogots make Ninh Binh province became inland HaLong Bay. In the study area most wide spread karst forms are: mogots, karst slope and peaks, karst remnant relief, karst relict relief, karst polje, karst dry valley and karst ponor and sinkholes. Because of tropical climate, limestones in the study area undergone a strong chemical weathering process, created many wonderful and diverse landscapes on the surface and cave system underground. Many caves of different size and forms were developed underground of limestone mountains at different altitudes. Caves of Yen Mo-Tam Diep area were investigated and mapped for tourism developing. Many caves have a culture-historical significant such as: Hang Mat, Tam Giao, Tra Tu, Ong Mich, Ma Tien, Chua Hang, Hang Doi and Hang But. A study results is contribution to planning, exploration a tourism potential of Ninh Binh province as well as to kart investigation in the region. Keywords: karst, mogot, caves, karst relief, speleothern.